Clinical practice guidelines for the management of enteral nutrition in the very low birth weight preterm neonate of the Peruvian Social Security (EsSalud) - Torres Salinas, Carlos Hugo (2024)
Introduction: This article summarizes the clinical practice guideline (CPG) for the management of enteral nutrition in premature newborns with very low birth weight in the Social Security of Peru (EsSalud). Objective: Provide evidence-based clinical recommendations for the management of premature newborns with very low birth weight in EsSalud. Methods: A guideline development group (GDG) was formed that included medical specialists and methodologists. The GDG formulated 5 clinical questions to be answered by this CPG. Systematic searches were carried out for systematic reviews and – when considered relevant – primary studies in Medline and CENTRAL during 2021. The evidence was selected to answer each of the clinical questions posed. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic working meetings, the GDG used the GRADE methodology to review the evidence and formulate recommendations, good clinical practice points, and the management flowchart. Finally, the CPG was approved with Resolution No. 071–IETSI-ESSALUD-2022. Results: This CPG addressed 5 clinical questions, all referring to the management of enteral nutrition in premature newborns with very low birth weight. Based on these questions, 5 recommendations were formulated (1 strong recommendation and 4 conditional recommendations), 5 GCP, and 1 flow chart. Conclusion: This article summarizes the methodology and evidence-based conclusions of the CPG for the management of enteral nutrition in premature newborns with very low birth weight in EsSalud.